Improving Speaking Skill Of The Tenth Grade Students Of SMK 17 Agustus 1945 Muncar Through Direct Practice With The Native Speaker - Mohamad Nor Shodiq (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
The Classroom Action Research (CAR) aims to invent teaching and learning strategy which fits the learners’ style and to solve the teachers’ problem in finding the appropriate technique in teaching. The researcher took SMK 17 Agustus 1945 Muncar Banyuwangi on 35 students of the tenth grade of AK 1 and was conducted in one cycle with the phases of planning, implementing, observing, and reflecting. The researcher found that the implementation of Direct Practice with the Native Speaker could improve the students’ speaking skill. It was proved by the result of the students’ speaking score. The average classical score in preliminary study was 50. 00.They had improvement from the third meeting but did not all of students meet the criteria of success and were still below the KKM. In the fourth meeting was found that all of the students could reach criteria of success and KKM score as 70.00. Direct Practice with the Native Speaker creates the teaching and learning process fun, and good atmosphere of competition among the students.